(17)O Relaxation Times in the Rat Brain at 16.4T - Wiesner, Hannes M. (Magn Reson Med, 2015)
PURPOSE: Measurement of the cerebral metabolic rate of oxygen (CMRO(2)) via direct imaging of the (17)O signal can be a valuable tool in neuroscientific research. However, knowledge of the longitudinal and transverse relaxation times of different brain tissue types is required, which is difficult to obtain because of the low sensitivity of natural abundance H(2)(17)O measurements. METHODS: Using the improved sensitivity at a field strength of 16.4 T, relaxation time measurements in the rat brain were performed in vivo and postmortem with relatively high spatial resolutions, using a chemical shift imaging sequence. RESULTS: In vivo relaxation times of rat brain were found to be T(1) = 6.84 ± 0.67 ms and T(2)* = 1.77 ± 0.04 ms. Postmortem H(2)(17)O relaxometry at enriched concentrations after inhalation of (17)O(2) showed similar T(2)* values for gray (1.87 ± 0.04 ms) and white matter, significantly longer than muscle (1.27 ± 0.05 ms) and shorter than CSF (2.30 ± 0.16 ms). CONCLUSION: Relaxation times of brain H(2)(17)O were measured for the first time in vivo in different types of tissues with high spatial resolution. Since the relaxation times of H(2)(17)O are expected to be independent of field strength, our results should help in optimizing the acquisition parameters for experiments also at other MRI field strengths.